FILTRASI AIR RAWA GAMBUT DENGAN PADUAN PERLIT-SEMEN-KAPUR - Hermansyah Aziz; Yennie Puspa Bukasir; Dwi Puryanti (Jurnal Riset Kimia, 2007)
ABSTRACT  Peat water purification by filtration with perlite-cement-lime mixtures was preliminary studied. The  filtration was realized under static condition without any pressure.  From the experimental results obtained that perlite composition in the mixture plays an important role in the filtration processing. Otherwise the some physical properties of perlite-cement-lime mixture was also determined. Key words: peat water, perlite.